2010
DOI: 10.1175/2009jcli3202.1
|View full text |Cite
|
Sign up to set email alerts
|

Why Is ENSO Influencing Northwest India Winter Precipitation in Recent Decades?

Abstract: This study examines decadal changes of the El Niñ o-Southern Oscillation (ENSO) influence on the interannual variability of northwest India winter precipitation (NWIWP). The analysis is based on correlations and regressions performed using India Meteorological Department (IMD) records based on station data and reanalysis fields from 1950 to 2008. The authors find that the interannual variability of NWIWP is influenced by the ENSO phenomenon in the recent decades. This conclusion is supported by a consistency a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 38 publications
2
59
0
Order By: Relevance
“…Lang and Barros (2004) found the PE to significantly influence geopotential height in the WWD track affecting CH. The AO, PE and ENSO have previously been linked to modifications of the wintertime westerly jet as well as precipitation totals over the KH (Syed et al 2006;Yadav et al 2010). Yadav et al (2010) found a statistically significant correlation between the Niño 3.4 index and northwest India precipitation for the period 1968-2008, with an increasingly strong correlation for the period .…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…Lang and Barros (2004) found the PE to significantly influence geopotential height in the WWD track affecting CH. The AO, PE and ENSO have previously been linked to modifications of the wintertime westerly jet as well as precipitation totals over the KH (Syed et al 2006;Yadav et al 2010). Yadav et al (2010) found a statistically significant correlation between the Niño 3.4 index and northwest India precipitation for the period 1968-2008, with an increasingly strong correlation for the period .…”
Section: Introductionmentioning
confidence: 79%
“…The AO, PE and ENSO have previously been linked to modifications of the wintertime westerly jet as well as precipitation totals over the KH (Syed et al 2006;Yadav et al 2010). Yadav et al (2010) found a statistically significant correlation between the Niño 3.4 index and northwest India precipitation for the period 1968-2008, with an increasingly strong correlation for the period . In this work, we also consider the SH, which is a predominant thermal high positioned over northern continental Asia.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…In the earlier studies by Yadav et al (2007Yadav et al ( , 2009aYadav et al ( , 2009bYadav et al ( , 2010 1900 1910 1920 1930 1940 1950 1960 1970 1980 1990 2000 …”
Section: Decadal Variability Of Nwiwpmentioning
confidence: 95%